Credit constraints, organizational choice, and returns to capital: Evidence from a rural industrial cluster in China - Ruan, Jianqing; Zhang, Xiaobo (International Food Policy Research Institute, 2008)
Traditional economic theory posits that a well-functioning capital market is a necessary condition for industrialization and economic growth. In reality, micro and small enterprises are ubiquitous because entrepreneurs can undertake low-return activities with minimal barriers to entry. Using a cashmere sweater cluster in China as an example, this paper shows that organizational choice can overcome the prohibitive cost of investment. When facing credit constraints, firms are more likely to concentrate in divisible production technologies in the form of industrial clusters. Within clusters, a vertically-integrated production process can be decomposed into many small incremental stages that are more accessible for the small entrepreneurs widely available in rural China, thereby supporting industrialization even in the absence of a well-functioning capital market. The observed rate of returns to capital is closely related to the organizational choice under credit constraints.